The Cambridge handbook of immunities and international law / edited by Tom Ruys, Nicolas Angelet, Luca Ferro. - Ruys, Tom; Angelet, Nicolas; Ferro, Luca (Cambridge University Press, 2019)
Few topics of international law speak to the imagination as much as international immunities. Questions pertaining to immunity from jurisdiction or execution under international law surface on a frequent basis before national courts, including at the highest levels of the judicial branch and before international courts or tribunals. Nevertheless, international immunity law is and remains a challenging field for practitioners and scholars alike. Challenges stem in part from the uncertainty pertaining to the customary content of some immunity regimes said to be in a 'state of flux', the divergent - and at times directly conflicting - approaches to immunity in different national and international jurisdictions, or the increasing intolerance towards impunity that has accompanied the advance of international criminal law and human rights law. Composed of thirty-four expertly written contributions, the present volume uniquely provides a comprehensive tour d'horizon of international immunity law, traversing a wealth of national and international practice.